S-Amlodipine: An Isomer with Difference—Time to Shift from Racemic Amlodipine - Jamshed Dalal; J. C. Mohan; S. S. Iyengar; Jagdish Hiremath; Immaneni Sathyamurthy; Sandeep Bansal; Dhiman Kahali; Arup Dasbiswas (International Journal of Hypertension)
Calcium channel blockers are among the first-line drugs for treatment of hypertension (HTN). S-amlodipine (S-AM), an S-enantiomer of amlodipine, is available in India and in other countries like China, Korea, Russia, Ukraine, and Nepal. Being clinically researched for nearly two decades, we performed in-depth review of S-AM. This review discusses clinical evidence from total 42 studies (26 randomized controlled trials, 14 observational studies, and 2 meta-analyses) corroborating over 7400 patients treated with S-AM. Efficacy and safety of S-AM in HTN in comparison to racemic amlodipine, used as monotherapy and in combination with other antihypertensives, efficacy in angina, and pleiotropic benefits with S-AM, are discussed in this review.